2016
DOI: 10.1378/chest.15-1504
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Enlargement Is Associated With Cardiac Injury During Severe Exacerbations of COPD

Abstract: BACKGROUND: Relative pulmonary arterial enlargement, defined by a pulmonary artery to aorta (PA/A) ratio > 1 on CT scanning, predicts hospitalization for acute exacerbations of COPD (AECOPD). However, it is unclear how AECOPD affect the PA/A ratio. We hypothesized that the PA/A ratio would increase at the time of AECOPD and that a ratio > 1 would be associated with worse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
45
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 47 publications
5
45
1
2
Order By: Relevance
“…Study conducted by Iyer et al's showed pulmonary artery enlargement correlated with pulmonary hypertension in COPD patients . In another study, which is consistent with the findings of our study, pulmonary artery enlargement correlated with increased exacerbation risk in COPD patients …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Study conducted by Iyer et al's showed pulmonary artery enlargement correlated with pulmonary hypertension in COPD patients . In another study, which is consistent with the findings of our study, pulmonary artery enlargement correlated with increased exacerbation risk in COPD patients …”
Section: Discussionsupporting
confidence: 93%
“…In this study, our results showed that there was the negative correlation between FEV1 and P‐A ratio in stable COPD patients. Pulmonary artery enlargement maybe reflects lung parenchyma destruction, hypoxia, air trapping, centralization of blood flow and loss of blood volume in small pulmonary vessels . The decreased of FEV1 in this study maybe, at least in part, resulting from lung parenchyma destruction.…”
Section: Discussionmentioning
confidence: 56%
“…PH in COPD is associated with markedly reduced survival but PA measurements on CT have not been studied in this context. Interestingly, a recent study comparing CT measured PA diameters at exacerbation and stable state, suggested an acute increase in PA diameter was observed at exacerbation and associated with elevation of cardiac biomarkers …”
mentioning
confidence: 99%
“…Recently, there has been significant interest in the use of CT in COPD, with several studies evaluating the utility of the ratio of the pulmonary artery to ascending aortic diameter (PA:A ratio) and pulmonary arterial enlargement [1519]. The PA:A has been calculated in several cohorts of healthy patients and those with different chronic respiratory conditions, and correlates with PA pressures as measured by RHC [9, 1517, 2022] and worsening clinical outcomes [15, 17, 18, 20, 21, 2325]. In a cohort of very severe COPD patients, the PA:A correlated with invasive haemodynamics, and a PA:A >1 independently predicted PH defined as a mean PA pressure >25 mmHg at right heart catheterisation with a sensitivity of 73% and a specificity of 84% [16].…”
mentioning
confidence: 99%
“…In a cohort of very severe COPD patients, the PA:A correlated with invasive haemodynamics, and a PA:A >1 independently predicted PH defined as a mean PA pressure >25 mmHg at right heart catheterisation with a sensitivity of 73% and a specificity of 84% [16]. Moreover, its presence was independently associated with an increased risk of severe COPD exacerbations [17] and an increased risk of cardiac injury and in-hospital mortality in individuals hospitalised with COPD exacerbations [18]. The PA:A ratio also predicts increased mortality in patients with advanced lung disease; a PA:A>1 was significantly associated with an increased risk of mortality in patients with very severe COPD who were undergoing evaluation for lung transplantation [15].…”
mentioning
confidence: 99%